A New Approach To Semantic Matchmaking Using Description Logics - Taibi, Toufik (INFOCOMP Journal of Computer Science, 2010)
An agent wishing to delegate some of its tasks to others needs to use the services of a matchmaking agent. The quality of the matchmaking process represents a key success factor in the effectiveness of the delegation process. As more services are exposing descriptions based on languages developed in the framework of Semantic Web, there is no doubt that Descriptions Logics (DLs) on which Web Ontology Language (OWL-DL) is based will be playing a major role in this context. This work contributes to the field in three ways. First, the DL ALCN was used in a matchmaking process that yields a justified ranking of results. Second, the matchmaking process provides useful information to the requester/provider in order to modify or refine the original request/capability description for a better result. Third, the requester agents should be able to further filter the results based on other criteria that we call “service goodness” that are based on some Quality of Service (QoS) criteria as well as attributes such as trust and cost.